129k views
2 votes
Please help me solve this. I don’t remember learning this

Please help me solve this. I don’t remember learning this-example-1
User Amfasis
by
6.7k points

1 Answer

2 votes

D)\text{ d}

Step-by-step explanation

let's remember some properties of the exponents and radicals


\begin{gathered} a^{(1)/(m)}=\sqrt[m]{a} \\ a^{(n)/(m)}=\sqrt[m]{a^n} \\ a^m*a^n=a^(m+n) \end{gathered}

so

Step 1

given


√(d^2)

hence, let's apply the rule


√(d^2)=d^{(2)/(2)}=d^1=d

therefore,the answer is


D)\text{ d}

I hope this helps you

User Jeyaganesh
by
5.9k points